Peran Pendidikan Teologi Berbingkai Moderasi Beragama Dalam Pengembangan Sikap Toleransi Mahasiswa - Pasaribu, Andar Gunawan (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2023)
Theological education in the frame of religious moderation is urgently needed now. Theological education in the framework of religious moderation means theological education which teaches and implements in four indicators, namely National Commitment, religious tolerance, anti-violence and accommodating local culture. The Old Testament has also implemented religious moderation with the implementation of the word מתינות דתית. While the New Testament uses the word metriopàqeia. Jesus showed an attitude of religious moderation but distanced himself from syncretism. Paul also shows an attitude of religious moderation. The method used is a qualitative method with literature and question to 10 pastor as resources. Pendidikan Teologi berbingkai moderasi beragama sangat berperan dalam pengembangan sikap tolerasnsi mahasiswa. Pendidikan teologi berbingkai moderasi beragama berarti Pendidikan Teologi yang mengajarkan dan mengimplementasi dalam empat indikator yaitu Komitmen Kebangsaan, toleransi beragama, anti kekerasan dan akomodatif kebudayaan Lokal. Perjanjian Lama juga sudah menerapkan moderasi beragama dengan implementasi dari kata מתינות דתית. Sedangkan Perjanjian Baru memakai kata metriopàqeia. Yesus menunjukan sikap moderasi beragama tetapi menjauhkan diri dari sinkritisme. Paulus juga menunjukan sikap moderasi beragama. Metode yang dipakai adalah kualitatif dan membuat pertanyaan kepada 10 orag pendeta.